Morphological, cultural and ecological characterization of Monilinia spp., pathogens of stone fruit in Serbia - Hrustić, Jovana; Mihajlović, Milica; Tanović, Brankica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2020)
Different brown rot pathogens cause similar symptoms on fruit, which makes it difficult to differentiate them based only on developed symptoms. Therefore, several methods have been described for accurate identification of Monilinia species. In spite of the fact that those methods can be reliable, there are several limitations for their use, and the aim of this study was to find out if there are any specific characteristics that could be used as additional features for precise identification and in-depth characterization of Monilinia species. The results showed that morphological characteristics on PDA, and mycelium growth rate on PDA medium can be useful characters for differentiation of Monilinia species since M. fructicola was found to grow faster than the other two test species, while M. fructigena grew the slowest. MALT was the optimal medium for M. laxa and M. fructigena isolates, while PDA medium was optimal for M. fructicola. Regarding an extremely acidic medium (pH 2), only M. laxa and M. fructicola isolates were able to grow in it, while M. fructigena isolate was the only that grew in a moderately alkaline medium (pH 9). Also, the results revealed that the optimal temperature for M. fructigena and M. fructicola growth was 23ºC, while 28ºC was optimal for M. laxa isolate. On the other hand, some differences in the sensitivity of Monilinia isolates were revealed at extreme temperatures: M. fructigena isolate was the most sensitive (grew from 4°C to up to 31°C), while M. fructicola isolate was the most resistant (grew at 2°C and 34°C). The obtained results inferred that there are no specific features that can be used for reliable and precise identification of Monilinia species, but we observed some differences regarding the effects of extreme temperatures and pH values of culture medium on different species. Further research, involving more isolates, is needed for a final conclusion.
Keywords: stone fruit, brown rot, Monilinia, Serbia